Anchoring Groups Determine Conductance, Thermopower and Thermoelectric Figure of Merit of an Organic Molecular Junction - Ramezani Akbarabadi, Saeideh; Madadi Asl, Mojtaba (Frontiers in Physics, 2021)
Transport properties of molecular junctions are prone to chemical or conformational modifications‎. Perturbation of the molecule-electrode coupling with anchoring groups or functionalization of the molecule with side groups is a well-characterized method to modulate the thermoelectric properties of molecular junctions‎. ‎In this study‎, ‎we used wide-band (WB) approximation combined with the non-equilibrium Green's function (NEGF) formalism to inspect conductance‎, ‎thermopower and figure of merit of an anthracene molecule coupled to gold (Au) electrodes‎. ‎To provide a comparative study, ‎three different anchoring groups were used‎, ‎i.e.‎, ‎thiol‎, ‎isocyanide and cyanide‎. ‎The molecule was then perturbed with the amine side group in two positions to explore the interplay between anchoring groups and the side group‎. ‎We showed that the introduction of side group alters transmission probability near the Fermi energy where transmission peaks are shifted relative to the Fermi level compared to the unperturbed molecule (i.e‎. ‎without side group)‎, ‎ultimately leading to modified electrical and thermoelectric properties‎. ‎The greatest value of electrical conductance was achieved when the side-group-perturbed molecule was anchored with isocyanide‎, ‎whereas the thiol-terminated molecule perturbed with the side group yielded the greatest value of thermal conductance‎. ‎We found that the Wiedemann-Franz law is violated in the Au-anthracene-Au device‎. ‎Furthermore‎, ‎the highest thermopower and figure of merit were attained in the cyanide-terminated perturbed molecule‎. ‎Our results indicate that charge donating/accepting character of the anchoring group and its interplay with the side group position can modify temperature dependency of conductance‎, ‎thermopower and figure of merit which is in agreement with experimental findings in organic molecular junctions. ‎Such modifications may potentially contribute to the understanding of emerging conductance-based memory devices designed to mimic the behavior of brain-like synapses‎.